A review of the genus Chaeridiona Baly, 1869 (Coleoptera: Chrysomelidae: Cassidinae) - Staines, C. L. (Zootaxa, 2007)
The genus Chaeridiona Baly is reviewed. All species, except Ch. pseudometallica Basu 1999, are redescribed and illustrated. Chaeridiona tuberculata Chen & Yu 1964, a homonym of Ch. tuberculata Uhmann 1961, is transferred to Prionispa and renamed Prionispa cheni, nom. novum. Chaeridiona clavata Yu, 1992 is transferred to Prionispa. Chaeridiona cupreovirida Gressitt is removed from synonymy. Chaeridiona angulata, new species, is described from Laos. A key to the species is provided.